Análise da influência do tipo e número de retenções no pilar de prótese cimentada sobre implante na discrepância marginal e resistência à remoção por tração - Saraiva, Leonardo Nogueira (2009)
This work aimed to analyze the marginal discrepancy and the resistance to traction remotion of precast columns to cemented prosthesis to implants, over the influence of the type and amount of retention, located on the axial wall of these implants. In order to do that, three groups were created: G1-Flat (Control), G2- Retention in the groove and G3- Retention in Slice. Groups G2 and G3 were divided then in six subgroups (three for each group), according to the amount of retention found on the column , ranging from one (a) , two (b) and three (c) for the same type of retentive. Waxed copings were also used over the columns and they were casted in cobalt-chromium alloy. For cementation, the cementing agent Temp Bond-Kerr was used, manipulated and added to copings according to the manufacturer's instructions. The marginal misfit was measured with an optical microscope before and after cementation. In order to carry out resistance tests to traction remotion, a universal testing machine with traction speed of 0.5 mm / min was used. The obtained results were analyzed by analysis of variance and Tukey s test, showing that when the number of deductions is increased, the marginal misfit is increased as well, except the 2nd subgroup (one groove), which had no statistically significant difference from the G1. G3 had the highest mean marginal discrepancy. Concerning the resistance to removal by traction, there was no significant difference between G1 and G2. G3 also showed greater increase when compared to other groups, however, its subgroups showed no significant difference between them.